1985
DOI: 10.1073/pnas.82.19.6637
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a human tumor necrosis factor from the LuKII cell line.

Abstract: A factor with tumor necrosis factor (TNF) activity produced by the LuKII human lymphoblastoid cell line [designated TNF(LuKII)] was purified sequentially by using controlled-pore glass, lentil lectin-Sepharose, and procion red agarose chromatography, yielding TNF with a specific activity of 1.5 X 10(7) units per mg of protein and an isoelectric point of approximately equal to 6.7. Purified TNF(LuKII) fractionated by NaDodSO4/PAGE under reducing as well as nonreducing conditions was found to contain seven prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…As the cytotoxin TNF was originally named for a protein produced in erndotoxin-treated mice (1), most studies of TNF have focused on induction by endotoxin, although certain mitogens and phorbol myristate acetate have also been shown to induce TNF (34). Even though Rmultiple closely-related TNFs may exist (4,17), the deduced amino acid sequences for mature TNF cloned from the tumor-derived HL-60 (3, 4) and U-937 (6) cell lines and lung macrophages (7) A recent study (36) has also shown that Sendai virus induces peripheral blood mononuclear cells to express a cytotoxin, which is believed to be TNF on the basis of neutralization of cytotoxic activity with a recombinant TNF n,onoclonal antibody. That report, however, may offer evidence for the existence of a cytotoxin closely-related to the cloned TNF, since the majority of the cytotoxic activity in that study eluted on a gel filtration column with a relative molecular mass of approximately 14,000 daltons.…”
Section: D-i-s-czs ¶Io1mentioning
confidence: 99%
See 2 more Smart Citations
“…As the cytotoxin TNF was originally named for a protein produced in erndotoxin-treated mice (1), most studies of TNF have focused on induction by endotoxin, although certain mitogens and phorbol myristate acetate have also been shown to induce TNF (34). Even though Rmultiple closely-related TNFs may exist (4,17), the deduced amino acid sequences for mature TNF cloned from the tumor-derived HL-60 (3, 4) and U-937 (6) cell lines and lung macrophages (7) A recent study (36) has also shown that Sendai virus induces peripheral blood mononuclear cells to express a cytotoxin, which is believed to be TNF on the basis of neutralization of cytotoxic activity with a recombinant TNF n,onoclonal antibody. That report, however, may offer evidence for the existence of a cytotoxin closely-related to the cloned TNF, since the majority of the cytotoxic activity in that study eluted on a gel filtration column with a relative molecular mass of approximately 14,000 daltons.…”
Section: D-i-s-czs ¶Io1mentioning
confidence: 99%
“…Cytotoxins produced by the immurne system are a heterogeneous group of proteins, the nature of which depends upon the variety of inducing agent and target cell involved (16)(17)(18)33). As the cytotoxin TNF was originally named for a protein produced in erndotoxin-treated mice (1), most studies of TNF have focused on induction by endotoxin, although certain mitogens and phorbol myristate acetate have also been shown to induce TNF (34).…”
Section: D-i-s-czs ¶Io1mentioning
confidence: 99%
See 1 more Smart Citation
“…1, lanes 3,4,6,7). TNF-/3 components with high molecular weight observed by others working with iodilmted protein [12] thus most likely also represent artefacts of the preparation.…”
Section: N-and O-glycosylationmentioning
confidence: 99%
“…)tt results, with molecular masses varying between 20 and 70 kDa [2,10,11]. In several studies, heterogeneous preparations were obtained, with up to seven bands with apparent masses between 19 and 80 kDa [12]. Various groups, using radiolabelled preparations, provided evidence that TNF-fl is N-glycosylated and possibly also O-glycosylated [13-i5].…”
Section: Tumor Necrosis Factor Beta (Tnf-fl) or Lymphotoxin Is A Cymentioning
confidence: 99%